Deregulation of selected microRNAs in sinonasal carcinoma: Value of miR-21 as prognostic biomarker in sinonasal squamous cell carcinoma - Kovarikova, Helena; Bubancova, Ivana; Laco, Jan; Sieglova, Katerina; Vosmikova, Hana; Vosmik, Milan; Dundr, Pavel; Nemejcova, Kristyna; Michalek, Jaroslav; Palicka, Vladimir; Chmelarova, Marcela (Head & neck, 2017)
BACKGROUND: Tumors occurring in the sinonasal area are characterized by unfavorable outcome due to difficult diagnosis, treatment, and prognosis of the disease corresponding with the anatomic complexity of the area. METHODS: We used quantitative real-time polymerase chain reaction (PCR) to compare relative expression of miR-21, miR-141, and miR-200c in 70 formalin-fixed, paraffin-embedded samples of sinonasal carcinoma tissue (majority of squamous cell carcinoma [SCC] samples) with 17 control samples of sinonasal tissue. RESULTS: Our data showed significant upregulation of miR-21 in sinonasal cancer tissue. Expression levels of miR-141 and miR-200c were below detectable levels in both sinonasal cancer samples and healthy tissue. Kaplan-Meier analysis with log-rank survival showed that patients with SCC with high expression of miR-21 (highest quartile) had impaired survival close to reaching statistical significance (P = .0630). CONCLUSION: Our results suggest that miR-21 upregulation is involved in tumorigenesis of sinonasal carcinoma and that it is associated with poor prognosis. Thus, miR-21 could be used as a valuable prognostic biomarker.
Keywords: senioři; head and neck cancer; analýza přežití; Reproducibility of Results; jehlová biopsie; Up-Regulation; Gene Expression Profiling; spinocelulární karcinom; Real-Time Polymerase Chain Reaction; Statistics, Nonparametric; reprodukovatelnost výsledků; Male; Analysis of Variance; Survival Analysis; upregulace; Prognosis; regulace genové exprese u nádorů; imunohistochemie; mikro RNA; nádory vedlejších dutin nosních; Kaplan-Meier Estimate; Biopsy, Needle; Middle Aged; mužské pohlaví; studie případů a kontrol; Kaplanův-Meierův odhad; neparametrická statistika; analýza rozptylu; MicroRNAs; kvantitativní polymerázová řetězová reakce; Biomarkers, Tumor; miR-21; Immunohistochemistry; biomarker; ženské pohlaví; nádorové biomarkery; prognóza; sinonasal carcinoma; Humans; Gene Expression Regulation, Neoplastic; Paranasal Sinus Neoplasms; microRNA; lidé středního věku; stanovení celkové genové exprese; Carcinoma, Squamous Cell; Female; Aged; lidé; Case-Control Studies